If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 8x + 12 Reorder the terms: 9 + 5x = 8x + 12 Reorder the terms: 9 + 5x = 12 + 8x Solving 9 + 5x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + 5x + -8x = 12 + 8x + -8x Combine like terms: 5x + -8x = -3x 9 + -3x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -3x = 12 + 0 9 + -3x = 12 Add '-9' to each side of the equation. 9 + -9 + -3x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 12 + -9 -3x = 12 + -9 Combine like terms: 12 + -9 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| -21+x=-85 | | (-14i)(-8i)=0 | | 68x-2=(50x+4)+15x | | 6y+3+3y-5= | | 5(1n-1)=7 | | 6=z/4-3 | | 11-5+5/-2 | | (8x+5)(8x+5)=4 | | 5y-2=2y-19 | | 431x=3574299 | | -2.3=u/4+4.1 | | 2(x+5)=10x-14 | | -35=x-5 | | 2=2+5v+2v | | -5-n=10 | | -3+12+6= | | 0.78=logx | | 8(x+1)=7(x+2) | | 2/7(21) | | 7(x-3)=8(4-2x) | | 5x-1=6x+7 | | 7(x-2)=-5 | | (2x+1)(3x-9)=0 | | 68x-25=(50x+4)+15x | | 52=3(-n-8)-2(1-8n) | | 47-y=205 | | 3n+6/3=5 | | 66=-6(-5+x) | | x^2+70x-1050=0 | | 5(2x+1)=10 | | 13x-4=12x-1 | | P=2l+2wfore |